(untitled) (Bangladesh Journal of Otorhinolaryngology, 2025)
Background: A common endocrine condition with a range of clinical manifestations and outcomes is primary hyperparathyroidism. The purpose of this study was to assess the surgical results for primary hyperparathyroidism. Aim of the study: The Aim of the study is to assess the outcome of surgery for primary hyperparathyroidism. Methods: A prospective observational study was conducted in the Head and Neck Surgery Division of the Department of Otolaryngology-Head & Neck Surgery, BSMMU, Shahbag, Dhaka from August 2022 to January 2023. 35 patients underwent parathyroidectomy. The data was collected and analyzed using SPSS 26.0 (Statistical Package for the Social Science). The statistical significance was set to p<0.05. Result: In this series, the majority of the patients (19, 54.29%) were in the 58 to 68 years age group. Among them, the majority (71.0%) of the patients were female. It was observed that the majority (54%) of the study subjects were symptomatic and 46% of the patients were asymptomatic.Here, 3 (8.5%), 6 (17.1%), and 2 (5.7%) patients presented with osteitis fibrosa cystica, nephrolithiasis, and neuropsychiatric syndrome respectively. Moreover, 14 (40.0%) patients had muscle weakness, and 18 (51.0%) subjects presented with fatigue. In this study, parathyroid adenoma was found in 85.75% and 74.90% of patients in symptomatic and asymptomatic patients respectively.The most affected site of the parathyroid gland was the right inferior lobe (13, 37.14%), followed by, the left inferior (31.42%), right superior (6, 17.14%), left superior (5, 14.28%).Preoperative PTH and calcium levels, and postoperative calcium levels in SPHPT and ASPHPT were found statistically significant. The majority of the patients (4, 11.42%) suffered from temporary hypocalcemia. A statistically significant increase in the Visual Analog Scale (VAS) score from 70 (interquartile range (IQR): 50-80) to 80 (IQR: 70-90) (P < 0.001). Conclusion:The long-term benefits of parathyroidectomy in patients with primary hyperparathyroidism (PHPT) are demonstrated by this prospective study. In the long run, these patients’ lives appear to be significantly impacted by the noted decrease in pre-operative symptoms. Bangladesh J Otorhinolaryngology 2024; 30 (2): 68-75